How could knowledge of sensemaking during organizational change contribute to the investigation of how sense is made of organizational perfomance - Allen, Richard (Cranfield University, 2011)
Managers and organizational stakeholders are confronted by a range of stimuli, emotions, events, data, paradoxes and ambiguities in endeavouring to understand and make sense of change and the performance of their organizations. However, there is virtually no literature available on sensemaking within organizational performance. Historically sensemaking literature has focused on unusual events, disasters and high reliability settings but there is now a sizeable body addressing sensemaking in strategic organizational change. This literature has been systematically reviewed because of its proximity to organizational performance and in order to assess how sensemaking in organizational performance could be in investigated. Sensemaking in individuals is triggered by the unusual and confounding and is concerned with how people construct meaning from this. While sensegiving is about the role played by leaders, or stakeholders, in generating, articulating and “selling” a construction or interpretation of events emerging from their own sensemaking process. “Mindfulness” can be thought of as how sensemaking is realised and is about responding rather than reacting while using information, attentiveness and clues to make sense of what is happening. The sensemaking studies reviewed are dominated by work with middle managers who are seen by the authors as key organizational change agents. Organizational actors come to sensemaking through mental maps, or schemata that can be re-configured through the sensemaking process often as a way of addressing paradox or equivocation. The view of sensemaking as inter-subjective, discursive and narrative dominates giving scope to managers to facilitate the process. Sensegiving and sensemaking intertwine dialectically in a process which sees sensemaking informing sensegiving and vice versa. There is insufficient information on mindfulness and change to be able to assess it. In conclusion there are sufficient similarities between the processes of organizational change and organizational performance management to warrant its investigation from an inter-subjective, discursive and narrative sensemaking perspective.
Keywords: Discursive; Interpretative; Inter-subjective; Mindfulness; Schema; Sensegiving